Prevalence of Human Papillomavirus and Genotype Distribution in Pregnant and Non-Pregnant Women in China - Luo D; Peng M; Wei X; Pan D; Xue H; Xu Y; Dong B (Dove Medical Press, 2021)
Dandan Luo,1 Meilian Peng,2 Xizhen Wei,1 Diling Pan,3 Huifeng Xue,4 Yuying Xu,1 Binhua Dong2 1Department of Obstetrics, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People's Republic of China; 2Department of Gynecology, Laboratory of Gynecologic Oncology, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People's Republic of China; 3Department of Pathology, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People's Republic of China; 4Fujian Provincial Cervical Disease Diagnosis and Treatment Health Center, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People's Republic of ChinaCorrespondence: Binhua DongDepartment of Gynecology, Laboratory of Gynecologic Oncology, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, 18 Daoshan Road, Fuzhou, Fujian, People's Republic of ChinaTel +86-591-87558732Fax +86-591- 87551247Email dbh18-jy@126.comYuying XuDepartment of Obstetrics, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, 18 Daoshan Road, Fuzhou, Fujian, People's Republic of ChinaTel +86-591-87279515Fax +86-591-87551247Email yyxu703@163.comPurpose: The status of human papillomavirus (HPV) infection in pregnant and non-pregnant women in China remains unclear. This study aimed to compare the prevalence and genotype distributions of HPV between pregnant and non-pregnant women in China.Patients and Methods: A case-control study was conducted of pregnant women during the second trimester and age-matched non-pregnant women attending the Fujian Maternity and Child Health Hospital between January 1, 2017 and December 31, 2018. Participants underwent cervical cytology testing and HPV genotyping. The genotyping test was able to identify 14 high-risk HPV (HR-HPV), four possible HR-HPV, and five low-risk HPV (LR-HPV) types. Further colposcopy and a cervical biopsy were performed if indicated. The primary outcomes were HPV prevalence and genotype distribution.Results: In total, 1077 pregnant and 1077 non-pregnant women were enrolled. Compared with non-pregnant women, pregnant women had a higher prevalence of HPV (24.2% vs 14.8%), HR-HPV (20.2% vs 11.7%), and LR-HPV (8% vs 4.5%) infection. In pregnant women, the most prevalent HPV genotypes were HPV-52 (6.0%), -16 (3.5%), -58 (2.6%), -53 (2.5%), and -51 (2.5%), while in non-pregnant women the most prevalent genotypes were HPV-52 (3.6%), -81 (1.9%), -51 (1.8%), -68 (1.4%), and -16 (1.3%). In women aged ≥ 35 years, HR-HPV (P=0.002) and LR-HPV (P=0.001) prevalence were significantly higher in pregnant women. However, in women aged < 35 years, only HR-HPV prevalence was higher in pregnant women. Pregnant and non-pregnant women with HPV-16 and HPV-58 infection had a high prevalence of high-grade squamous intra-epithelial lesions (HSIL) (HPV-16: P< 0.001 and P=0.005, HPV-58: P=0.043 and P=0.005); but with other HR-HPV genotypes, only non-pregnant women had an increased HSIL prevalence.Conclusion: In China, the HPV prevalence is higher in pregnant women than that in non-pregnant women and is also age- and genotype-dependent. HPV-infected pregnant women aged ≥ 35 years and those with HPV-16 should be closely monitored to enable rapid clinical intervention.Keywords: human papillomavirus, genotype, squamous intraepithelial lesions, cervical cytology, China, pregnant